2006
DOI: 10.1128/jvi.80.1.426-439.2006
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transduction with Recombinant Adeno-Associated Virus Is Primarily Restricted by Capsid Serotype Not Vector Genotype

Abstract: We and others have recently reported highly efficient liver gene transfer with adeno-associated virus 8 (AAV-8) pseudotypes, i.e., AAV-2 genomes packaged into AAV-8 capsids. Here we studied whether liver transduction could be further enhanced by using viral DNA packaging sequences (inverted terminal repeats [ITRs]) derived from AAV genotypes other than 2. To this end, we generated two sets of vector constructs carrying expression cassettes embedding a gfp gene or the human factor IX (hfIX) gene flanked by ITRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
90
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 75 publications
5
90
0
Order By: Relevance
“…A high percentage of hepatocytes showed immunohistochemical evidence of a decrease in intracellular Z-AAT, which is consistent with earlier studies by a number of groups, indicating that rAAV8-pseudotyped vectors are quite efficient for transduction of murine liver. 19,28,41,42 In fact, the inability of the original rAAV2-based vectors Software, sections for each rAAV8-siRNA transduced livers were analyzed. Thresholded area represents the area on the section that is within the parameters considered to be positive staining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high percentage of hepatocytes showed immunohistochemical evidence of a decrease in intracellular Z-AAT, which is consistent with earlier studies by a number of groups, indicating that rAAV8-pseudotyped vectors are quite efficient for transduction of murine liver. 19,28,41,42 In fact, the inability of the original rAAV2-based vectors Software, sections for each rAAV8-siRNA transduced livers were analyzed. Thresholded area represents the area on the section that is within the parameters considered to be positive staining.…”
Section: Discussionmentioning
confidence: 99%
“…19,[24][25][26][27][28] In this report, a number of small-interfering RNA (siRNA) constructs directed against AAT were expressed from rAAV vectors in vitro and in vivo and their ability to decrease the levels of intracellular Z-AAT within the liver was assessed. A tri-functional (3X) construct emerged from these studies as a potential candidate for future studies of gene therapy of AAT liver disease.…”
mentioning
confidence: 99%
“…However, attempts by Kay and colleagues to improve liver-directed AAV gene transfer efficiency by modifying the vector DNA (i.e. ITRs) among serotypes AAV1 to AAV6 were unsuccessful, [3] whereas switching vector capsid significantly influences vector performance [2,4,5].Cumulative evidence from preclinical and clinical studies using AAV vectors has demonstrated that the vector capsid is not only critical in determining the tropism and transduction efficiency, but also is a major antigen whose interaction with host immune responses will determine both the ability of the vector to access the target tissue and the resulting duration of expression.The work by VandenDriessche and colleagues in this issue of the Journal [6], together with recent reports [7][8][9], characterizes a new player in the AAV arena: AAV9 isolated from human tissues, another vivid example of what a capsid change can achieve in gene transfer experiments. These authors demonstrate that, similar to AAV8, AAV9 is effective in transducing hepatocytes of hemophilia B mice, which resulted in supraphysiological levels of biologically active factor (F) IX.…”
mentioning
confidence: 99%
“…Studies in adult mice have shown that partial hepatectomy, which is associated with a burst of hepatocellular proliferation, leads to rapid loss of episomal vector genomes. [14][15][16] Essentially the same phenomenon is seen following vector delivery to neonatal mice, where high rates of hepatocellular proliferation result in almost complete clearance of episomal vector genomes within two doublings of liver mass occurring within the first 1-2 weeks of life. 17,18 A stable basal level of transgene expression, probably reflecting vector integration, persists thereafter in up to 8% of hepatocytes depending on the vector dose used.…”
Section: Impact Of Proliferation In Target Cell Populationsmentioning
confidence: 84%